Learning Resource Development: An Online-Based Learning for Indonesian Teachers - SOFYAN SOFYAN; DAMERIA SINAGA; RUBIATI RUBIATI (Universitas Jambi, Indonesia, 2020)
The purpose of this study was to develop an online-based learning resource for Indonesian language teachers. The development step started with the identification of learning objectives, learning process, analysis of learning resources and environments, formulation of specific objectives, design of assessment instruments and learning strategies, selection and development of teaching materials, design and evaluation of formative development projects, and making of good terms. The findings showed that the formative evaluations by experts showed the agreements of 89.23% from educational technology experts, 97.50% from material experts, and 90.00% from multimedia experts. The agreements informed that the online-based learning could be recommended for Indonesian language teachers. Furthermore, the average results of individual trials were 89.21%, small group trials (97.13%), and field trials (89.04%). The online-based learning resource established in this research and development study was feasible and useable. Implications of the findings are also discussed.